Ushnus of the Inca provincial region: An analysis of two ceremonial platforms from Inca sites in Catamarca (Argentina) - Lynch, Julieta (2013)
We present in this manuscript a 4 year survey of meteor shower radiants utilizing the Southern Argentina Agile Meteor Radar (SAAMER). SAAMER, which operates at the southern most region of South America, is a new generation SKiYMET system designed with significant differences from typical meteor radars including high transmitted power and an 8-antenna transmitting array enabling large detected rates at low zenith angles. We applied the statistical methodology developed by Jones and Jones (Jones, J., Jones, W. [2006]. Month. Not. R. Astron. Soc. 367, 1050–1056) to the data collected each day and compiled the results into 1 composite representative year at 1° resolution in Solar Longitude. We then search for enhancements in the activity which last for at least 3 days and evolve temporally as is expected from a meteor shower. Using this methodology, we have identified in our data 32 shower radiants, two of which were not part of the IAU commission 22 meteor shower working list. Recently, SAAMER’s capabilities were enhanced by adding two remote stations to receive meteor forward scatter signals from meteor trails and thus enable the determination of meteoroid orbital parameters. SAAMER started recording orbits in January 2012 and future surveys will focus on the search for unknown meteor streams, in particular in the southern ecliptic sky.